2013
DOI: 10.1089/jamp.2011.0941
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Switching Tiotropium HandiHaler® to Respimat® Soft Mist Inhaler in Patients with COPD: The Difference of Adverse Events and Usability Between Inhaler Devices

Abstract: There was no major problem in switching from tiotropium HandiHaler to Respimat. Respimat and HandiHaler showed similar effects and usability. However, we should be aware of cough just after inhalation with Respimat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 6 publications
2
15
0
1
Order By: Relevance
“…Although they are pharmacologically inert, they can produce a cold sensation that may cause the patient to stop inhaling 24. SMIs do not require propellants,41 and excipients are minimized. The delivery of the drug as a mist aerosol avoids the cool sensation from evaporating gases that can be experienced with pMDIs 16.…”
Section: Requirements Of the “Ideal” Inhalermentioning
confidence: 99%
“…Although they are pharmacologically inert, they can produce a cold sensation that may cause the patient to stop inhaling 24. SMIs do not require propellants,41 and excipients are minimized. The delivery of the drug as a mist aerosol avoids the cool sensation from evaporating gases that can be experienced with pMDIs 16.…”
Section: Requirements Of the “Ideal” Inhalermentioning
confidence: 99%
“…In TABLE 7, the author has reported some studies where LAMA/device systems are compared in terms of preference, usability, inhaler use, satisfaction with use and willingness to continue the inhaler use [49,75,135,[142][143][144][145][146][147][148][149][150][151][152][153][154][155][156][157]. Unfortunately, these outcomes were assessed in various ways, ranging from a simple question to non-validated and validated proprietary questionnaires.…”
Section: Devicementioning
confidence: 99%
“…In addition, successful drug delivery to the lungs (as determined by a physician) is associated with patient satisfaction with their inhaler device; satisfaction promotes long-term compliance with respiratory maintenance therapy and is linked to improved clinical outcomes [1,3,[45][46][47]. Assessments conducted during clinical trials and studies using self-report instruments [including simple surveys specific to Respimat Ò , the validated Patient Satisfaction and Preference Questionnaire (PASAPQ) and the Handling Questionnaire (an investigational tool)] have suggested that patients with COPD or asthma find Respimat Ò easy to operate [3,45,[48][49][50][51][52][53] and prefer this inhaler over other types of device, such as pMDIs or DPIs [3,[49][50][51][52]54].…”
Section: Respimatmentioning
confidence: 99%